Gray matter–related proteins are associated with childhood-onset multiple sclerosis. Issue 5 (October 2015) - Singh, Vaibhav; van Pelt, E. Daniëlle; Stoop, Marcel P.; Stingl, Christoph; Ketelslegers, Immy A.; Neuteboom, Rinze F.; Catsman-Berrevoets, Coriene E.; Luider, Theo M.; Hintzen, Rogier Q.
Abstract : Objective: To identify CSF biomarkers for multiple sclerosis (MS) in children with an initial acquired CNS demyelinating syndrome (ADS). Methods: CSF was collected from a cohort of 39 children with initial ADS, 18 of whom were diagnosed with MS and 21 of whom had a monophasic disease course. Proteomic analysis of trypsinized CSF (20 μL) was performed by nano-liquid chromatography Orbitrap mass spectrometry. Univariate statistical analysis was used to identify differentially abundant proteins between childhood-onset MS and monophasic ADS. Results: A total of 2, 260 peptides corresponding to 318 proteins were identified in the total set of samples. Of these 2, 260 peptides, 88 were identified as being most distinctive between MS and ADS. Fifty-three peptides, corresponding to 14 proteins, had higher abundance in children with MS compared to children with monophasic ADS. Twelve of these 14 proteins were linked to neuronal functions and structures, such as synapses, axons, and CNS proteases (e.g., neurofascin, carboxypeptidase E, brevican core protein, and contactin-2). The other 2 were functionally related to immune function. The 35 peptides identified with decreased abundance in children with MS corresponded to 7 proteins. Six of them were linked to innate immune function (e.g., haptoglobin, haptoglobin-related protein, C4b-binding protein alpha chain, and monocyte differentiation antigen CD14) and 1 was linked to cellular adhesion (protein diaphanous homolog 1). Conclusion: At first onset of ADS, CSF of children diagnosed with MS showed increased abundance of CNS gray matter–related proteins, whereas CSF of children with a monophasic disease course showed increased abundance of innate immunity–related proteins.